Understanding tourism in Nigeria - Falade, Oladele (Ibadan : JIS Printing Press, 1999)
This documentation on tourism in Nigeria provides a compendium of information on Nigeria Tourist Potentials. A study of this text will allow the appreciation of our natural heritage and the role this can play in development of people and places in our Nation. Indeed understanding Tourism is really understanding and appreciating ourselves as a Nation. This text is valuable for teachers, students and researchers on tourism as well as administrators and policy makers concerned with the development of tourism in Nigeria.
Includes bibliographical references (p. 181-184).
rpm 22/09/16
Loans
Keywords: Tourism; Nigeria